Health of Soil Supporting Vegetable Cultivation in Peri-Urban Areas. Issue 1 (2nd January 2016) - Sharma, R. P.; Singh, R. S.; Singh, S. K.; Naik, P. S.; Singh, B.
Abstract: In developing countries, wastewater is used to irrigate vegetables in small- and large-scale production where potable water is scarce. Sustainability of vegetable production depends on development of farming systems that can at least arrest soil deterioration and sustain soil fertility. Soil quality was used for a study on farming systems in India. This article examined soil properties in vegetable fields to evaluate effects of past land use on these properties and assess how changes could affect soil health on peri-urban land. Bioremediation, washing of vegetables with clean water, discouraging cultivation of heavy metal–accumulating leafy vegetables, and avoidance of fertilizers and pesticides with high heavy metals are a few ways to promote safe vegetable production in peri-urban areas where contamination can be a problem.